Absolute and relative risk prediction in cardiovascular primary prevention with a modified SCORE chart incorporating ceramide-phospholipid risk score and diabetes mellitus. Issue 3 (13th July 2021) - Hilvo, Mika; Jylhä, Antti; Lääperi, Mitja; Jousilahti, Pekka; Laaksonen, Reijo
Abstract: Aims: A risk score, CERT2, based on distinct ceramide and phosphatidylcholine lipid species, has shown robust performance in predicting cardiovascular risk in secondary prevention. Here, our aim was to investigate the predictive value of CERT2 in primary prevention compared to classical lipid biomarkers and its compatibility with clinical characteristics used in the SCORE risk chart. Methods and results: Four ceramides [Cer(d18:1/16:0), Cer(d18:1/18:0), Cer(d18:1/24:0), Cer(d18:1/24:1)] and three phosphatidylcholines [PC(14:0/22:6), PC(16:0/22:5), PC(16:0/16:0)] were analysed by targeted tandem liquid chromatography–mass spectrometry method in FINRISK 2002, which is a population-based risk factor survey investigating men and women aged 25–74 years. Primary prevention subjects ( N = 7324) were followed up for 10 years for the following outcomes: incident coronary heart disease (CHD), cardiovascular disease (CVD), major adverse cardiovascular event (MACE), stroke, and heart failure. Hazard ratios per standard deviation obtained from adjusted Cox proportional hazard models were significant for all these endpoints, and the highest for fatal ones, i.e. fatal CHD [1.45 (95% confidence interval 1.07–1.97)], CVD [1.39 (1.06–1.83)], and MACE [1.39 (1.07–1.80)]. The categorical net reclassification improvement was 0.051 for the 10-year risk of incident CVD. Incidence of fatal events was over 10-fold more frequent in the highest CERT2 category compared to the lowest risk category and modified SCORE risk charts, utilizing CERT2 and diabetes mellitus, increased granularity of risk assessment compared to a chart utilizing total cholesterol. Conclusion: CERT2 is a significant predictor of incident cardiovascular outcomes and risk charts utilizing this score provide an easy tool to estimate relative and absolute risk for incident CVD. Graphical Abstract: